Enhanced recovery after cesarean delivery & role of anesthesiologists: A narrative review - Samina Ismail; Malika Hameed (Wolters Kluwer Medknow Publications, 2023)
Enhanced recovery after cesarean delivery (ERAC) is an evidence-based interdisciplinary protocol with an aim to improve quality of care and patient satisfaction while lowering health care cost by reducing length of hospital stay. It is an approach that combines several evidence-based perioperative care components to hasten patient recovery. ERAC uses multidisciplinary approach with inclusion of all stakeholders including anesthesiologists, obstetricians, pediatricians, nurses, pharmacists, patients, and hospital administration. Therefore, institutional support, local infrastructure, and compliance of all supporting systems are necessary for the successful implementation of ERAC. The role of anesthesiologists in implementation of standardized care cannot be disregarded as they are involved in the provision of perioperative services to improve maternal outcomes and healthcare quality. The purpose of this narrative review is to explore the components and guidelines from the enhanced recovery after surgery for caesarean delivery, highlight the responsibility of anesthesiologists in the existing and emerging ERAC programs and the difficulties associated with implementing the ERAC in resource-constrained environments.